PHYTOMYMIC NAMES IN ENGLISH FOLKLORE - Matkarimova Gulira'no Abdullayevna (Western European Studies, 2025)
This article analyzes the use of phytomymic names in English folklore. Phytonyms are reflected in various stable expressions, proverbs, and riddles, encompassing important information about the culture, history, and traditions of the people. The article examines the role and semantic features of phytonyms in English folklore based on the works of authors such as Donald Watts, Thomas Thistleton Dyer, William Shakespeare, Ben Jonson, and Michael Drayton. The mythological and literary context of phytonyms is also analyzed, shedding light on their historical development.
Keywords: phytonym; folklore; English literature